Post-exercise effects of cold water immersion and contrast water therapy - Part 2: Acute effects of contrast water therapy and passive recovery on the physical and haematological parameters in male university rugby players over a 48-hour recovery period - Broodryk, A.; Coetzee, B.; Pienaar, C.; Sparks, M. (African Journal for Physical, Health Education, Recreation and Dance, 2017)
The purpose of this study was to determine the effects of contrast water therapy (CWT) and passive recovery (PAR) on various haematological and physical components of male universitylevel rugby players after an intense fitness session. Twenty-three rugby players were randomly assigned to either a control (PAR) or experimental (CWT) group. Following a 15 minute-long fitness session, the CWT-group alternated between warm water (40-42 C; 3 minutes), and cold water (8±1 C; 1 minute), during the 20-minute recovery period, while the PAR-group remained seated. Haematological and physical components were evaluated at baseline, 0 hours post-fitness training, and at 0, 24 and 48 hours post-recovery. Haemoglobin and blood lactate (BLa-) showed a significant decrease (p=0.05), whereas plasma glucose and partial oxygen level (PO2) showed a significant increase from 0 to 24 hours in both the CWT and PAR groups. In the CWT group, six variables (BLa-, haemoglobin, vertical jump test (VJT) height, VJT peak-power, VJT peak speed and grip strength) returned to baseline values 0 hours post-CWT, whereas the PAR group demonstrated recuperation at 0 hours in four variables (BLa-, VJT height, VJT peak speed and grip strength). Plasma glucose was restored after 24 hours for the CWT group, whereas the PAR group only demonstrated baseline values after 48 hours. A significant variance between the CWT and PAR groups were observed in BLa- and grip strength (F(1,21)>4, p=0.05) at various time points. Compared to PAR, CWT caused a larger percentage recovery in specific haematological and physical components, which would suggest that CWT is superior to PAR as an acute recovery modality.